Stock Market Linkage, Financial Contagion and Assets Price Movements: Evidence from Nigerian Stock Exchange - ABDULLAHI, Shafiu Ibrahim (Journal of Advanced Studies in Finance; Vol 8 No 2 (2017): JASF Volume VIII Issue 2(16) Winter 2017DO - 10.14505//jasf.v8.2(16).04, 2018)
This paper studied portfolio-investments diversification, stock market linkage and negative integration in Nigerian stock exchange. Like many other stock exchanges around the world, Nigerian stock exchange was devastated by the global financial crisis of 2008. That single crisis has changed the mode of operations of the market by affecting market capitalisation, efficiency and profit. Ten stock market indices are involved in this study, where the aim is to find out how Nigerian stock markets relate with counterparts around the world. The study covered the period from September 2009 to August 2016. The study used Generalised Impulse response function, Engel-Granger cointegration and Johansen cointegration analysis to measure integration between Nigerian stock exchange and selection of nine stock exchanges around the world. The results from cointegration analysis show lack of cointegration. This means despite globalisation Nigerian stock exchange is less integrated with the rest of the stock markets providing ample opportunities for portfolio diversification. This also further support previous studies that found out that developed countries stock markets tend to correlate with their developed countries counterparts than emerging and developing markets.